Analysis of the Relationship Between Nurse Burnout Levels and the Quality of Nursing Services - Devira, Gesya Amo (Trigin Institute, 2024)
This study examines the relationship between nurse burnout levels and the quality of nursing services, highlighting the critical impact of burnout on both job performance and patient care outcomes. Utilizing a mixed-methods approach, quantitative data were collected through the Maslach Burnout Inventory to assess emotional exhaustion, depersonalization, and personal accomplishment among a diverse sample of registered nurses across various healthcare settings. Qualitative insights were garnered from semi-structured interviews and focus groups to explore perceptions of nursing service quality. The findings reveal a significant correlation between high burnout levels and decreased job performance, with nurses reporting challenges in communication, patient engagement, and overall care effectiveness. Systemic factors such as inadequate staffing and lack of managerial support were identified as major contributors to burnout, emphasizing the need for organizational reforms. This research underscores the importance of addressing nurse burnout not only for the well-being of nursing professionals but also for enhancing the quality of patient care. Recommendations for targeted interventions and policy initiatives are discussed, aiming to foster a healthier work environment and improve patient outcomes within the healthcare system.